ANALISA KINERJA PERSIMPANGAN BERSINYAL PADA PERSIMPANGAN ANGKATAN 66 DAN RUAS JALAN R. SOEKAMTO KOTA PALEMBANG - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
Transportation is a very important and strategic means to facilitate the movement in an effort to meet the needs of the community. Planning and construction of transportation facilities and infrastructure, greatly influence in determining the increase of economic growth in supporting the achievement of development targets. The real impact that occurs as a result of rapid economic growth, population growth, and changes in land use affects the performance of intersections and roads, especially the problem of congestion, delays, queues opportunities and other issues. Based on the result of calculation analysis which have been done by using Indonesian Highway Capacity Manual method (IHCM), capacity of intersection of Angkatan 66 Palembang on the condition of the morning peak was 3007 smp / hour at peak lunch was 2875 smp / hour and the afternoon peak is 2997 smp / hour. The high movement of vehicular traffic flow at the intersection of Angkatan 66 and the road R. Soekamto indicates that the level of service is not sufficient to meet traffic needs, this can be seen from the Lower level of service or performance (Level of Service / LOS) at the intersection Angkatan 66 and the road R. Soekamto C (0,7908) and D (0,889) are at the level where the current begins unstable operation speed relatively quick decline due to the obstacles that arise. So to overcome the problem of alternative road widening or construction of fly over (fly over) and traffic management in the form of traffic engineering management has to be implemented.